Impact of exercise to treat postural orthostatic tachycardia syndrome: a systematic review - Cortez, Melissa M.; Aikins, Kayla; Arnold, Amy C.; Boris, Jeffrey R.; Davenport, Todd E.; Johnson, Katie; Kattaya, Hagar S.; Kinsella, Laurence; McFarland, Mary M.; Pelo, Ryan; Powers, Clayton D.; Schiltz, Kelsi; et al. (Frontiers in Neurology, 2025)
BackgroundPostural orthostatic tachycardia syndrome (POTS) is a chronic condition associated with a high symptom burden and decreased quality of life (QOL). Exercise is currently considered to be a first line non-pharmacological treatment for POTS. The purpose of this systematic review was to evaluate the impact of exercise on cardiovascular and patient-centered outcomes in patients with POTS.PurposeTo evaluate whether exercise benefits patients with POTS by synthesizing data from published clinical studies.MethodsElectronic databases, including Medline, Embase, CINAHL Complete, Cochrane CENTRAL, and others were searched and results were exported on May 2, 2023. Study inclusion: those that utilized an exercise program as an intervention for POTS and were conducted as experimental or quasi-experimental design. Exclusions: Non-English language papers and opinion-based/theoretical/non-empirical studies/case reports. Data extraction was based on Cochrane Handbook guidance and summarized according to Synthesis Without Meta-analysis (SWiM) guidelines; methodological quality and risk of bias was evaluated using the JBI Critical Appraisal tools. Standardized effects were calculated and summarized based on the direction of effect.ResultsSeven studies included in the final review are described in the data summary and synthesis. Improvements in heart rate were reported across all studies reviewed, while stroke volume and QOL improvements were also found. Notably, not all studies reported on the latter two outcomes. Methodological variability across studies precluded meta-analysis, and risk of bias was considered moderate-high in all but a single study.ConclusionWhile currently available evidence supports exercise as beneficial to QOL and cardiovascular features of POTS, we identified a major need for additional studies assessing the effect of exercise on symptom burden and daily function, including studies that consider patients with specific comorbidities that impact exercise tolerability and/or dosing.